2009
DOI: 10.2298/sarh0912619d
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and relevance of concomitant diseases in elderly patients hospitalized for community acquired pneumonia

Abstract: The patients aged over 65 years hospitalized due to community acquired pneumonia had a statistically significantly higher prognostic score, mortality rate and concomitant diseases than the patients below 65 yeas of age. Most subjects of the older group of patients had two or three comorbidities. Concomitant diseases resulted in a statistically significant hospital mortality elevation. When comborbitities involved chronic obstructive pulmonary disease and decompensated cardiomyopathy, a statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Although sensitivity analysis was performed by excluding the retrospective observational studies, the influence of methodological quality (study design) on bias was still unknown. Moreover, four cohort studies [34][35][36][37] and one case-control study 38 were included in the metaanalysis, in which one cohort study 34 did not document the ascertainment of CAP, and the other four studies divided CAP patients into patients who died or patients who survived, and were thus excluded from our review. In addition, that meta-analysis focused exclusively on mortality, the other clinically important outcomes including length of hospital stay, ICU admission and need for mechanical ventilation were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although sensitivity analysis was performed by excluding the retrospective observational studies, the influence of methodological quality (study design) on bias was still unknown. Moreover, four cohort studies [34][35][36][37] and one case-control study 38 were included in the metaanalysis, in which one cohort study 34 did not document the ascertainment of CAP, and the other four studies divided CAP patients into patients who died or patients who survived, and were thus excluded from our review. In addition, that meta-analysis focused exclusively on mortality, the other clinically important outcomes including length of hospital stay, ICU admission and need for mechanical ventilation were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 13 relevant studies with 394 832 participants for inclusion in this analysis . Patients tended to be > 60 years of age, and predominantly male.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of study quality found that one was a post hoc analysis of a trial , five were retrospective observational studies , and seven were prospective observational studies . Radiographic confirmation of pneumonia was reported in 11 studies , while one study relied on International Classification of Disease (ICD‐10) codes , and another did not specify the exact method . COPD case definition was less certain, with only five studies explicitly specifying spirometric criteria, either before or after the pneumonia episode .…”
Section: Resultsmentioning
confidence: 99%